Diagnosis and Management of Autonomic Dysfunction in Dementia Syndromes - Allan, Louise M. (Curr Treat Options Neurol, 2019)
PURPOSE OF REVIEW: Autonomic dysfunction is common in dementia, particularly in the Lewy body dementias. This review considers the evidence for autonomic dysfunction in dementia, common symptoms and potential management options. RECENT FINDINGS: Autonomic dysfunction has been shown in Alzheimer’s disease and Lewy body dementias. Common symptoms include orthostatic dizziness, syncope, falls, urinary tract symptoms and constipation. Non-pharmacological management of orthostatic hypotension should include bolus water drinking. Pharmacological management may include the use of midodrine or droxidopa although the latter is not available in Europe. Atomoxetine is a noradrenaline reuptake inhibitor which may be useful if further clinical trials become available. Management of constipation may include the use o f probiotics, osmotic laxatives such as macrogol and chloride type 2 channel activators such as lubiprostone. Management of urinary tract symptoms may include the use of mirabegron. SUMMARY: There is a dearth of clinical trials for autonomic dysfunction in dementia and most of the evidence is imputed from trials in Parkinson’s disease. However, pragmatic recommendations may be made. There is a need for controlled clinical trials in people with dementia.